Efeito da não ablação no processo de reprodução de fêmeas de Penaeus vannamei - Menezes, Thiago Bastos Bezerra de (2019)
In Brazil, the reproduction of Penaeusvannamei is held in specialized hatchery. The hatchery is divided into two different sectors and it is composed by maturation and hatchery. In the reproduction phase, often times breeders that go through sexual maturation by eye ablation are used. However, the use of this technique might present a lot of disadvantages besides the reproduction, other physiological and metabolic processes are also affected by the withdrawal of the ocular peduncle. The use of non ablated females (NAF) has gotten much interest in the hatchery, due to the fact that they have a longer life than the ablated females (AF). Few studies evaluated the difference of productive between systems based in (AF) and (NAF). The goal of this study was to accomplish a comparative analysis of the ablation and non-ablation effects in the reproductive process of female shrimps from the P. vannemei species. The present study was developed in the CELM Aquicultura S.A. company. The breeders used were obtained from the breeders’ formation sector of the same company. Males and females of 33g and 39gwere used. In the quarantine sector, the animals had been stocked in densities up to 30/m³, where they remained for30 days. The females that went throughthe ablation process had been transferred to the maturation and copulation sector after 15 days. In this sector, the blocks 1 (NAF) and 2 (AF) were used each with 7 tanks. In each tank, 70 males and 90 females had been stocked. As the presence of spermatophores and the gonadal maturation were verified, the females had been transferred to the spawning sector, which is composedof 4 collective spawning tanks. After the spawning, the females had been transferred again to the maturation and copulation sector. Due to gravity,the spawning tanks had been drained for the carboys, where the eggs were washed and afterwardthey were taken to the hatching sector.In the hatching section, 12 carboys of 1.000L each were used for the hatch of the eggs. After the eggs’ hatch, the larvae were transferred to the nauplii room. Then, the nauplii were transferred to the larviculture sector. 8 rectangular tanks were used, with 25.000L each, and an initial density of 250 N3/L. It have been verified: Mortality rate (%), Daily copulation rate (%), Frequency of copulation (day), Spawning frequency (day), Spawning rate (%), Hatching rate (%), Number of eggs/female, Number of nauplii/female, where the NAF group presented superior values for Frequency of copulation (16,5 ± 4,7),Spawning frequency (17,8 ± 4,8),Spawning rate (92,7 ± 5,3),Hatch rate (70,8 ± 2,7),Number of eggs/female (297.208 ± 24.827ª)and Number of nauplii/female (210.625 ± 21.681).On the other hand, the AF group presented superior values forthe Mortality rate (39.1) and the Daily copulation rate (11,7 ±2.8). The present study has shown that the use of NAF turns into a reproductive performance similar to the procedure that uses the ablation technique. In addition, it has been verified that the non-ablation of females doesn’t implicatethe zootechnical performance in the larval phase.